(untitled) (Experimental biology, 2016)
In the State Register of selection achievements of the republic made only amylose rice varieties. Creating domestic glutinous rice for children and dietary nutrition is an important issue. For creating the first local glutinous rice varieties Kazakhstan low amylose content (glutinous) hybrids of different generations were obtained by using conventional breeding method (pneumo-castration and TVEL method of pollination).In greenhouse conditions at IPBB was received 2 generations of rice per year. Polygenic traits "amylose content" stabilized only F6-F7 generations. As a result, a comprehensive assessment by biochemical parameters and economically valuable traits isolated and characterized perspective glutinous hybrids F3-5 generation whose amylose content ranges from 2.4 to 15.6%.Most perspective for the creation of domestic glutinous varieties considered low amylose awnless variety group: var. minantica Gust, var. affnis Koern, var. fulva Piac, var. brunneo-punctata Gust, var. neroapiculata Gust.